Recommendations for the use of natriuretic peptides for early diagnosis of heart disease in patients with diabetes: A consensus report by SPEDM, SPC, NEDM-SPMI and APMGF - João Sérgio Neves; Rui Baptista; Estêvão Azevedo de Pape; Manuel Rodrigues Pereira; Rita Paulos; Jonathan Pinheiro dos Santos; Cristina Gavina; João Jácome de Castro (Revista Portuguesa de Cardiologia)
Diabetes mellitus is a significant risk factor for the development of heart disease (HD), with heart failure (HF) being one of the early manifestations of the disease in this population. The diagnostic process is challenging and contributes to a significant number of undiagnosed cases of HD among individuals with diabetes. This is largely due to the non-specific nature of symptoms and signs in the initial stages of disease, making early detection elusive. Timely identification and prevention of HD in patients with diabetes have the potential to significantly improve patient prognosis and alleviate the growing burden of this population on the national healthcare system.Natriuretic peptides (BNP and NT-proBNP) have been recognized as reliable, cost-effective biomarkers for detecting HD and can be further used as risk assessment biomarkers in asymptomatic patients. Despite being recommended in several European and American guidelines to rule-out and rule-in HF, the routine use of these biomarkers for the diagnosis of HDs in patients with diabetes has only recently been proposed by the American Diabetes Association (ADA) and has not yet been implemented in Portugal. Therefore, a multidisciplinary panel of experts from four medical societies, the Portuguese Society of Endocrinology, Diabetes and Metabolism, the Portuguese Society of Cardiology, the Diabetes Study Group from the Portuguese Society of Internal Medicine and the Portuguese Association of Family Medicine were convened to discuss and establish consensus recommendations for natriuretic peptide screening in patients with diabetes and its integration into routine diabetes management protocols.This manuscript draws on the consensus recommendations from four Portuguese medical societies, offering clear guidance on natriuretic peptides use tailored to Portuguese clinical practice. Accordingly, this consensus advises the use of NT-proBNP analysis for all patients with diabetes aged 50 years and older, or under 50 if they have risk factors and/or comorbidities. Adjusted rule-out and rule-in values for age, sex and risk factors are provided. NT-proBNP levels above 125 pg/mL should prompt additional testing and cardiovascular investigation. Routine evaluation every two to three years for low-risk patients and annually for high-risk patients is proposed when NT-proBNP is below 125 pg/mL and in the absence of suspected heart disease. Resumo: A diabetes mellitus é um fator de risco significativo para o desenvolvimento de doenças cardíacas, sendo a insuficiência cardíaca uma das primeiras manifestações da doença nesta população. O processo de diagnóstico é complexo e contribui para um número significativo de casos não diagnosticados de doença cardíaca em doentes diabéticos, devido à natureza não específica dos sintomas e sinais, ou à impossibilidade da sua deteção em fases iniciais da doença. A deteção precoce e a prevenção da doença cardíaca em doentes diabéticos poderão contribuir para melhorar significativamente o prognóstico dos doentes e reduzir os encargos crescentes desta população sobre o Sistema Nacional de Saúde.Os peptídeos natriuréticos (BNP e NT-proBNP) têm sido reconhecidos como fidedignos, rentáveis e com um peso relevante na deteção de doença cardíaca, podendo ser utilizados como biomarcadores para avaliação de risco em doentes assintomáticos. Apesar de serem recomendados em várias diretrizes europeias e americanas na exclusão ou identificação da insuficiência cardíaca, a utilização sistemática destes biomarcadores para o diagnóstico de doenças cardíacas em doentes diabéticos só recentemente foi proposta pela American Diabetes Association (ADA), não estando ainda em prática em Portugal. Como tal, foi reunido um painel de especialistas de quatro sociedades médicas portuguesas, a SPEDM (Sociedade Portuguesa de Endocrinologia, Diabetes e Metabolismo), SPC (Sociedade Portuguesa de Cardiologia), NEDM-SPMI (Núcleo de Estudos da Diabetes Mellitus da Sociedade Portuguesa de Medicina Interna) e APMGF (Associação Portuguesa de Medicina Geral e Familiar) com o objetivo de discutir e estabelecer recomendações de consenso para o rastreio de péptidos natriuréticos em doentes diabéticos, bem como a sua integração no protocolo de rotina de gestão da diabetes.Este manuscrito transpõe as recomendações de consenso das quatro sociedades médicas portuguesas, fornecendo orientações claras, e ajustadas à prática clínica portuguesa, sobre o uso dos peptídeos natriuréticos. É recomendada a análise do NT-proBNP em todos os doentes diabéticos com idade igual ou superior a 50 anos, ou inferior a 50 se tiverem fatores de risco e/ou comorbilidades. São fornecidos valores recomendados para exclusão e diagnóstico de doenças cardíacas na população diabética, tendo em conta a idade, sexo e outros fatores de risco. Os níveis de NT-proBNP superiores a 125 pg/mL devem motivar testes adicionais e investigação cardiovascular. Propõe-se uma avaliação de rotina a cada 2-3 anos para os doentes de baixo risco e anualmente para os doentes de alto risco quando o NT-proBNP é inferior a 125 pg/mL e na ausência de suspeita de doença cardíaca.